Characteristic energy range of electron scattering due to plasmaspheric hiss. Issue 12 (3rd December 2016) - Ma, Q.; Li, W.; Thorne, R. M.; Bortnik, J.; Reeves, G. D.; Kletzing, C. A.; Kurth, W. S.; Hospodarsky, G. B.; Spence, H. E.; Baker, D. N.; Blake, J. B.; Fennell, J. F.; et al.
Abstract: We investigate the characteristic energy range of electron flux decay due to the interaction with plasmaspheric hiss in the Earth's inner magnetosphere. The Van Allen Probes have measured the energetic electron flux decay profiles in the Earth's outer radiation belt during a quiet period following the geomagnetic storm that occurred on 7 November 2015. The observed energy of significant electron decay increases with decreasing L shell and is well correlated with the energy band corresponding to the first adiabatic invariant μ  = 4–200 MeV/G. The electron diffusion coefficients due to hiss scattering are calculated at L  = 2–6, and the modeled energy band of effective pitch angle scattering is also well correlated with the constant μ lines and is consistent with the observed energy range of electron decay. Using the previously developed statistical plasmaspheric hiss model during modestly disturbed periods, we perform a 2‐D Fokker‐Planck simulation of the electron phase space density evolution at L  = 3.5 and demonstrate that plasmaspheric hiss causes the significant decay of 100 keV–1 MeV electrons with the largest decay rate occurring at around 340 keV, forming anisotropic pitch angle distributions at lower energies and more flattened distributions at higher energies. Our study provides reasonable estimates of the electron populations that can be most significantly affected by plasmaspheric hiss and the consequent electron decay profiles. Key Points: The Van Allen Probes provide measurements of energy‐dependent electron decay profiles across different L shells The energy range of measured electron decay is consistent with plasmaspheric hiss‐induced pitch angle scattering Plasmaspheric hiss causes anisotropic pitch angle distribution at lower energies and more flattened distribution at higher energies